Apakah Sukuk Ritel Merupakan Ancaman Bagi penghimpunan Dana Pihak Ketiga Pada Bank Syariah? - Syakur,, Muhammad (Jurnal Ekonomi, 2020)
This research is a quantitative study that aims to consider the effect of retail sukuk on the collection of third parties funds (TPF) in Indonesian Islamic Banks for 2015 - 2019. The data used are secondary data retrieved from Islamic Banking Statistics Report for shariah commercial and unit shariah bank quarterly. The method is multiple linear regression analysis techniques with Ordinary Least Square (OLS) approach, using TPF as the dependent variable while Retail Sukuk, ROA, Promotion Cost, Inflation and Bi rate as the independent variables. The results shows Retail Sukuk has a negative and significant impact on the collection of TPF which is intended that retail sukuk is causing the decrease of TPF amount in Indonesian Islamic bank. Therefore the Indonesian government needs to review the policies related to retail sukuk issuance in order to synergize with the development of Islamic Banks. Other results indicate that ROA and promotion costs have positive and significant influance for TPF collection in Indonesian Islamic bank while BI rate is the opposite.